2015
DOI: 10.1016/j.enconman.2014.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol-enriched heterogeneous catalyst for biodiesel production from soybean oil and waste frying oil

Abstract: In the present work, biodiesel production using a glycerol enriched heterogeneous catalyst was studied. For that purpose, the catalyst performance at different glycerol concentrations and reaction conditions (under ambient atmosphere) was evaluated and two triglyceride sources were used. The most active catalyst was produced using CaO, glycerol and methanol at a mass ratio of 1:1.6:13.4, respectively. By per-forming the transesterification reaction under ambient atmosphere during 2 h at 333 K, using 0.4 wt.% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…The use of appropriate amount of glycerol for its adequate interaction with CaO is of high importance as confirmed also in the previous report that concluded the deactivation of catalyst because of availability of surplus amount of glycerol in the reaction mixture during its by-production during the methanolysis reaction [34]. Also, Ferrero et al [21] reported that glycerol dosage higher than the optimum amount resulted in decreasing of biodiesel yield. This study investigated the impact of different glycerol dosage (5, 10 and 15 wt% of CaO wt.)…”
Section: Glycerol Dose Effectmentioning
confidence: 54%
See 3 more Smart Citations
“…The use of appropriate amount of glycerol for its adequate interaction with CaO is of high importance as confirmed also in the previous report that concluded the deactivation of catalyst because of availability of surplus amount of glycerol in the reaction mixture during its by-production during the methanolysis reaction [34]. Also, Ferrero et al [21] reported that glycerol dosage higher than the optimum amount resulted in decreasing of biodiesel yield. This study investigated the impact of different glycerol dosage (5, 10 and 15 wt% of CaO wt.)…”
Section: Glycerol Dose Effectmentioning
confidence: 54%
“…This strategy ensured the elimination of even a minor possibility for the generation of catalytic methoxide species, and generated only glycerol-enriched CaO catalytic material. Previous studies have reported the formation of glycerol-enriched CaO species in the presence [21,22,32] and absence [18,27] of methanol. Understanding the reaction between CaO and methanol that results in the formation of calcium methoxide as reported by Kawashima et al [33] and well-known poisoning phenomenon of CaO because of atmospheric CO 2 and H 2 O, this study used an alternative method for the preparation of only glycerol-enriched CaO species in the presence of oil.…”
Section: Catalyst Type Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the stoichiometric equation, three moles of methanol is required to react with triglyceride and produced three moles of FAME and glycerol as the by-product [4]. Transesterification has been widely used to convert numerous oils into biodiesel including soybean oil [5], palm oil [6], sunflower oil [7], jatropha oil [8], and waste cooking oil (WCO) [9]. However, high cost of vegetable oil feedstock is the main concern for biodiesel production.…”
Section: Introductionmentioning
confidence: 99%